The Effect Of Compensation, Cooperation, Work Discipline On Employee Performance With Organizational Commitment As An Intervening Variable In PT Hki Binjai-Brandan Zone IV - Raden Annas Dio Rahman Kusumo; Kiki Faride Ferine; M. Isa Indrawan (International Journal of Management, Economic and Accounting, 2023)
The purpose of this study is to identify the effect of Compensation, Cooperation, Work Discipline on Employee Work Performance with Organizational Commitment as an Intervening Variable at PT Hutama Karya Infrastruktur Binjai-Brandan Zone IV. The approach to this study uses quantitative methods. The population in this study is all employees contained in PT HKI Binjai-Brandan Zone IV as many as 147 respondents. The sampling technique used by the author is purposive sampling with criteria so that the sample number is 70 respondents. The type of data used in this study is primary data using questionnaires or interviews. The analysis technique used is Structural Equation Modeling (SEM) using SmartPLS software. The results showed that adequate compensation can have a positive and significant impact on employee work performance. Cooperation in the workplace has a positive and significant impact on job performance. High discipline has a positive and significant influence on employee work performance. Compensation has a positive and significant relationship to organizational commitment. Compensation has a positive and significant effect on organizational commitment. Cooperation does not have a positive and significant effect on organizational commitment. High discipline can have a positive and significant impact on employees' organizational commitment. Compensation can have a positive and significant impact on employee performance through organizational commitment mechanisms. Cooperation does not have a positive and significant effect on employee performance through organizational commitment. Discipline has a positive and significant effect on employee performance through organizational commitment.